Querying framework documentation - Sansano, Mauricio (2001)
In this paper we discuss about the combination of to powerful tools for documenting object oriented frameworks: hypermedia navigational models and hypermedia queries. We also present a way for translating queries performed on top of framework documentation applications, into XML representations, as a way for exchanging framework documentation not only through the web, but through different information systems. Specially, we concentrate in integrating OOHDM, a model for designing object oriented hypermedia applications, with framework documentation applications having hypermedia features, and with OOHQL, an object oriented hypermedia query language that allows to perform queries on top of these kind of applications. Our intent is to describe an architecture that, integrating this elements, will allow to create easy-to-use framework documentation, capable of being exchanged through other systems and work teams. -- Keywords: OO-Frameworks, hypermedia queries, XML representation, documentation.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 13/03/2009)
International Workshop on Multimedia Data and Document Engineering (MDDE